Deregulation of circ_003912 contributes to pathogenesis of erosive oral lichen planus by via sponging microRNA-123, -647 and -31 and upregulating FOXP3 - Zhen Huang; Fen Liu; Wenjuan Wang; Shaobo Ouyang; Ting Sang; Zikun Huang; Lan Liao; Jun Wu (BMC, 2021)
Abstract Background The FOXP3/miR-146a/NF-κB axis was previously reported to modulate the induction and function of CD4+ Treg cells to alleviate oral lichen planus. Also, other signaling pathways including microRNA-155-IFN-γ loop and FOXP3/miR-146a/TRAF6 pathways were reported to be involved in the pathogenesis of oral lichen planus. In this study, we aimed to investigate the molecular mechanism underlying the pathogenesis of EOLP. Method CircRNA microarray was used to observe the expression of candidate circRNAs in CD4+ T-cells collected from different groups. Real-time PCR and Western blot were conducted to observe the changes in the expression of different miRNAs, mRNAs and proteins. Flow cytometry was performed to compare the counts of Treg cells in the HC and EOLP groups, and ELISA was performed to evaluate the changes in the expression of inflammatory cytokines. Result No obvious differences were seen between the HC and EOLP groups in terms of age and gender. Among all candidate circRNAs, the expression of circ_003912 was most dramatically elevated in CD4+ T-cells collected from the EOLP group. The levels of miR-1231, miR-31, miR-647, FOXP3 mRNA and miR-146a were decreased while the expression of TRAF6 mRNA was increased in CD4+ T-cells collected from the EOLP group. The count of Treg cells in the EOLP group was dramatically increased. The levels of inflammatory cytokines including IL-4 IFN-γ, IL-10 and IL-2 were influenced by the presence of circ_003912. In CD4+ T-cells in the EOLP group, the levels of IL-4 and IL-10 were decreased while the levels of IFN-γ and IL-2 were increased. The presence of miR-1231, miR-31 and miR-647 all obviously inhibited the expression of circ_003912, which was validated to sponge the expression of above miRNAs. Also, FOXP3 mRNA was proved to be targeted by miR-1231, miR-31 and miR-647. Transfection of circ_003912 up-regulated the expression of circ_003912, miR-146a and FOXP3 mRNA/protein while down-regulating the expression of miR-1231, miR-31, miR-647, and TRAF6 mRNA/protein. The levels of inflammatory cytokines including IL-4 IFN-γ, IL-10 and IL-2 as well as the speed of cell proliferation were influenced by circ_003912. Conclusion In this study, we investigated the molecular mechanisms underlying the pathogenesis of EOLP which involved the functioning of circ_003912. We first demonstrated that circ_003912 was up-regulated in CD4+ T-cells of the EOLP group. And miRNAs including miR-1231, miR-31 and miR-647 were sponged by circ_003912 and down-regulated in CD4+ T cells of the EOLP group, which subsequently up-regulated the expression of FOXP3 and miR-146a, and resulted in the inhibition of NF-kB.